Subject to Change - Social Work, Moral Regulation and recent debates on Alienation - Jan Düker (Social Work and Society, 2019)
The article explores 'alienation' (and its inverse 'appropriation') as a central category for analysing and normatively orienting social work. Social work is characterised as a context of institutionalised moral regulation which offers to individuals chances for as well as impediments to appropriation of 'the social'. A critique of Rahel Jaeggi's and Hartmut Rosa's theories of alienation serves as a reference to clarify the position of this article. The lack of an analysis of current social conditions and relationships as well as an overemphasis on transforming subjectivities to ameliorate alienation are identified as major problems pertaining to these theories, necessitating a material account of appropriation to identify which areas of life conduct should be subject to change and in which way subjectivity should change.